WAYS TO DEVELOP TOURISM IN THE ZOMINSUV RESERVOIR AREA THROUGH RA-TIONAL USE OF RECREATIONAL RESOURCES (Scientific journal of the Fergana State University, 2026)
This article examines the issues of large-scale tourism development in the Zominsuv Reservoir area through the rational use of recreational resources. In addition, the recreational resources of Zominsuv have been studied and analyzed according to their origin and usage characteristics, and they have been classified into three groups: natural, natural-anthropogenic, and anthropogenic.